Exploring the shared molecular mechanisms of primary hypertension and IgA vasculitis through a case report and combining bioinformatics analysis - Qijiao Wei; Jiayan Feng; Yifei Mu; Qian Shen; Hong Xu; Li Sun; Haimei Liu (Frontiers in Immunology)
BackgroundPrimary hypertension (PHTN) and IgA vasculitis (IgAV) are two prevalent medical conditions that affect the kidneys. Despite their distinct pathophysiological mechanisms, clinical manifestations, and treatment approaches, both conditions significantly impact patients’ quality of life and overall health. Unfortunately, a boy developed hypertensive nephritis (HN) at the age of 4, followed by IgAV nephritis at the age of 10. The exact pathophysiological mechanisms underlying these conditions remain elusive. This study aims to report this unusual case and investigate the biological mechanisms associated with the differentially expressed genes (DEGs) related to PHTN and IgAV through the application of bioinformatics tools.MethodsWe present the case of a boy diagnosed with PHTN and IgAV. Additionally, we explore the molecular mechanisms underlying both conditions. DEGs were analyzed, and gene functional enrichment was performed using the DAVID database. A protein-protein interaction (PPI) network was constructed using the STRING database and visualized with Cytoscape software. The hub genes were identified using the MCODE plugin. CIBERSORT was used to assess the expression changes in immune cells and obtain the proportion of various types of immune cells. Furthermore, the Connectivity Map L1000 platform was utilized to identify potential therapeutic agents.ResultsThe boy initially presented with malignant hypertension (MHT), and renal biopsy pathology indicated HN. Following regular use of antihypertensive medications, there was a significant improvement in blood pressure (BP), renal function, and the left ventricular hypertrophy index. However, he developed IgAV six years after the diagnosis of PHTN. A subsequent renal biopsy revealed IgAV nephritis, and the pathology associated with HN showed marked improvement. A total of 7,027 DEGs associated with PHTN and 90 DEGs linked to IgAV were identified, with 25 genes overlapping between the two sets. KEGG pathway analysis revealed that the DEGs were primarily associated with extracellular matrix (ECM) receptor interaction. Among EMC key components, fibronectin expression was markedly elevated in hypertensive nephritis and IgA nephropathy. Gene Ontology (GO) biological process analysis indicated that the 25 overlapping DEGs were significantly related to processes such as proteolysis, amyloid fibril formation, cAMP-mediated signaling, synaptic vesicle endocytosis, and receptor internalization. The significantly enriched terms related to changes in the cellular component of DEGs included platelet alpha granule membrane, nucleoplasm, and endocytic vesicle membrane. Changes in molecular function were primarily associated with protein binding. Furthermore, six hub genes implicated in both diseases were linked to cell adhesion molecules. We also found that neutrophils accounted for the majority of all infiltrating cells. And B cell naïve were downregulated in both diseases.Using the Connectivity Map (CMap) database, the top 10 potential therapeutic agents were identified.ConclusionWe found that aggressive BP-lowering agents were necessary for managing PHTN. This study also reveals the common pathogenesis underlying both PHTN and IgAV. Moving forward, these shared hub genes could serve as novel targets for more in-depth mechanistic investigations and the development of new therapeutic interventions for individuals affected by PHTN and IgAV.